REDUCING THE ANGLE OF ATTACK OF A THREE-AXLE BOGIE LOCOMOTIVES - Yevstratov, O. S.; Kossov, V. S. (Science and Transport Progress, 2004)
The mechanism of radial wheelset positioning due to the central acceleration provides efficient reduction of the angle of attack and of a lateral displacement. The results obtained theoretically are confirmed by tests.